P2X7 on Mouse T Cells: One Channel, Many Functions - Rissiek, Björn; Haag, Friedrich; Boyer, Olivier; Koch-Nolte, Friedrich; Adriouch, Sahil (Frontiers in Immunology, 2015)
The P2X7 receptor is an adenosine triphosphate (ATP)-gated cation channel that is expressed by several cells of the immune system. P2X7 is best known for its proinflammatory role in promoting inflammasome formation and release of mature interleukin (IL)-1β by innate immune cells. Mounting evidence indicates that P2X7 is also an important regulatory receptor of murine and human T cell functions. Murine T cells express a sensitive splice variant of P2X7 that can be activated either by non-covalent binding of ATP or, in the presence of nicotinamide adenine dinucleotide, by its covalent ADP-ribosylation catalyzed by the ecto-ADP-ribosyltransferase ARTC2.2. Prolonged activation of P2X7 by either one of these pathways triggers the induction of T cell death. Conversely, lower concentrations of ATP can activate P2X7 to enhance T cell proliferation and production of IL-2. In this review, we will highlight the molecular and cellular consequences of P2X7 activation on mouse T cells and its versatile role in T cell homeostasis and activation. Further, we will discuss important differences in the function of P2X7 on human and murine T cells.